PENERAPAN STORYTELLING INTERAKTIF SEBAGAI METODE KREATIF UNTUK MEMBANGUN LITERASI KRITIS PESERTA DIDIK - Sabrina Ais Zahra; Nurlaila Ana; Rozana, Afroh; Mar’atus Sholihah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
In this digital era, conventional learning methods need to be adapted to maintain student interest and promote critical literacy more strategically through an interactive narrative approach. This article aims to examine the implementation procedures of interactive narratives as well as the use of digital media in primary education to improve children's language skills, including listening abilities and speaking confidence. By applying descriptive analysis on various pedagogical models, this study highlights systematic stages in storytelling, starting from media preparation to students being able to tell stories independently. The analysis results indicate that the implementation of interactive narratives, especially with the use of digital media such as Canva and CapCut applications, can shift the role of students from passive receivers to active participants. This approach not only improves language skills and social competence, but also serves as a powerful means of instilling character values and preserving local culture. Therefore, the implementation of structured interactive narratives becomes a strong foundation for enhancing critical thinking skills, creativity, and strengthening the cultural identity of elementary school students in this digital era.